Current-Mode Rail-to Rail Instrumentation Amplifier for General Purpose Instrumentation Applications - Uğur Çini (International Journal of Applied Methods in Electronics and Computers, 2016)
Instrumentation amplifiers are used extensively in bio-potential reading, industrial sensor applications, Wheatstone bridge amplifiers etc. In this work, a high input common-mode range instrumentation amplifier is presented. The amplifier is composed of two second generation current conveyors (CCII+) with common-mode input range close to supply swings and a differential difference current conveyor (DDCC) at the second stage with high voltage swing at the output. Also an optional DC servo loop is employed as a feedback to second stage for the removal of any possible DC offset voltage at the output which can be used for AC coupled applications. The simple design strategy with high input common-mode range and nearly rail-to-rail output stage together with increased bandwidth advantage of current-mode approach makes the proposed implementation desirable for many of the general purpose instrumentation applications. The design is made using 0.35μm AMS technology with 3V supply voltage. The operation is verified by HSPICE simulations.